Policies of access and retention in higher education in Brazil: the program “Universidade para todos” - Dotta, Alexandre Godoy (Universidad Nacional del Litoral, 2020)
Explores the Brazilian public policies that deal with the promotion of access and retention of students in the university. Approaches the main actions done for this type of education and describes some of the lead changes that occurred in the educational policies for higher education in the governments of Fernando Henrique Cardoso (1995-2002) and Luiz Inácio Lula da Silva (2003-2010). Describes the creation process and the operation of the Program “Universidade para Todos” (PROUNI), settled by the Provisional Measure number 213 in 2004, before becoming the Law number 11.096 in 2005. Considers the creation of the Law number 10.861, the one that established SINAES (National System of Evaluation of the Higher Education) and ENADE (National Exam of Students’ Performance). Shows the report data and the tax expenditure from the Government Macro-Assessment Office of the Federal Court of Accounts. Presents amount of tax waiver from the State and describes the number of given scholarships by making an analysis of the annual and mensal costs for a single student of the program from 2005 to 2012; the number of dropouts of PROUNI scholarship holders from 2005 to 2009. Concludes indicating the main benefits and outcomes of the program.